Clinical efficacy of periosteal pedicle graft with subepithelial connective tissue graft in gingival recession coverage - Priyanka Prakash; Saroj K Rath; Manish Mukherjee (Wolters Kluwer Medknow Publications, 2019)
Introduction: Correction of gingival recession (GR) involves eliminating the cause of recession and it often requires surgical correction. Subepithelial connective tissue graft (SCTG) technique by Langer and Langer provides excellent esthetics and is considered most predictable in obtaining marginal tissue recession coverage. However, the requirement of a second surgical procedure for harvesting CTG remote from planned site of recession coverage increases the chances of postoperative infection. There is also a limitation in the amount of graft that can be harvested and an increased operative time contributing to patient discomfort. Materials and Methods: Overcoming these difficulties has become possible with the introduction of "periosteal pedicle graft" (PPG). The study is a split-mouth design where patients with bilateral, isolated GR defects were treated using two different surgical techniques, i.e., PPG versus the SCTG in obtaining GR coverage. The objective was to analyze the comparative amount of root coverage and the gain in width of attached gingiva achieved by both the techniques. Results: All the clinical parameters evaluated were comparable between SCTG and PPG when recorded at 6 and 9 months posttreatment. Conclusion: Both techniques produced satisfactory and predictable results. PPG eliminated the need for the 2nd operative site, lesser intraoperative time, and hence, patient comfort was enhanced.